Implementasi SEMA No. 3 Tahun 2023 Dalam Mempersulit Alasan Perceraian 'Perselisihan dan Pertengkaran yang Terus Menerus' Di Provinsi Banten. - Muhammad Fajri Atqiya; Fitria Agustin (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
This study aims to analyze the implementation of Supreme Court Circular Letter (SEMA) Number 3 of 2023 as an instrument to strengthen the principle of complicating divorce, especially in cases with the reason of "continuous disputes and quarrels" in Banten Province. The phenomenon of the high divorce rate in Indonesia, where 54% is caused by disputes, demands objective legal standardization. In Banten Province itself, data shows a significant trend of increasing cases from 2023 to the projected year 2025. This study uses a normative juridical method with a statutory approach to synchronize the policy of SEMA No. 3 of 2023 with Law Number 1 of 1974 concerning Marriage. The results of the study indicate that the determination of a minimum requirement of 6 (six) months of separation of residence is an effort by the Supreme Court to create a stricter legal filter to reduce the number of premature divorces. However, its implementation still faces serious challenges, including: low public legal literacy, the ineffectiveness of the mediation process which is still considered an administrative formality, and the potential for inconsistent decisions at the appellate level. This study concludes that although SEMA No. 3 of 2023 provides more objective legal certainty, optimizing the role of mediators and public education within the jurisdiction of Banten Province is key to this regulation's effective reduction in the divorce rate.